The Assessment of Long-Run Equilibrium between GDP, Exports and Foreign Investments in Armenia - Gabrielyan, Arman (Bulletin of Yerevan University G: Economics, 2016)
The purpose of this paper is to examine the dynamic interrelationships between real quantities of GDP, exports of goods and services, and inflow of foreign direct investments in Armenia, and to determine the causal relations among those three variables using vector error correction model and Granger causality test. Cointegration analysis indicates there are a long run dynamic equilibrium relationships between the variables under study, and in the case of disequilibrium only real GDP and real exports adjust with speeds of adjustment 0.29 and 0.18 respectively. Applying Granger causality test, we haven’t found causality running from FDI growth to GDP growth, though the reverse causality is significant at the 10% level. But there is statistically significant bidirectional causality between GDP and exports. The fact that in the error correction model the speed adjustment parameter for FDI isn’t statistically different from zero suggests about narrow opportunities for profitable investments.